Understanding Article 102b of the Governor of DKI Jakarta Regulation No. 70 Year 2021 Regarding the Second Amendment to the Governor of DKI Jakarta Regulation No. 132 of 2018 Regarding the Coaching of the Administration of Owned Apartment - Widjaja, Gunawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The Governor of DKI Jakarta Regulation No.70 Year 2021 regarding the Second Amendment to the Governor of DKI Jakarta Regulation No.132 Year 2018 regarding the Coaching of the Administration of Owned Apartment, which was issued on September 1, 2021, has made changes in several provisions in the previous Governor's Regulation. One of the changes is Article 102B. This study discusses the meaning of the change, thoughts on the implementation, and its transitions. This research is normative legal research, which uses secondary data. The analysis was carried out qualitatively through a descriptive-analytical approach to find answers to the objectives of this study. As a guide, this research conducts analysis using Gustav Radbruch’s perspective.